Perpetration of Intimate Partner Violence and COVID-19-Related Anxiety During the Second Lockdown in Portugal: The Mediating Role of Anxiety, Depression, and Stress - Cunha, Olga (Journal of family violence, 2024)
PurposeThe restrictions imposed during lockdown by COVID-19 pandemic entailed increased risks for the perpetration of intimate partner violence (IPV). Widespread fear and uncertainty related to the virus and the policies adopted to contain it have been linked to a set of social, emotional, and economic stressors that can increase the risk of IPV. The present study aims to assess the association between COVID-19-related anxiety, psychological distress (depression, anxiety, and stress), and IPV perpetration in the community, as well as to assess the mediating role of psychological distress and depression, anxiety, and stress in the relationship between COVID-19-related anxiety and the perpetration of IPV.MethodsA sample of 336 participants (282 females, Mage = 34.91, SD = 11.72) was recruited from the Portuguese population through an online self-report questionnaire, completed after the second lockdown (from April and July 2021).ResultsHigh rates of IPV perpetration during the confinement, in particular psychological and physical IPV, were found. COVID-19-related anxiety and psychological distress (depression, anxiety, and stress) were related to higher levels of IPV perpetration. Psychological distress and stress mediated the relationship between COVID-19-related anxiety and total IPV perpetration and psychological distress and depression mediated the relationship between COVID-19-related anxiety and psychological IPV perpetration.ConclusionsThis study highlights the mediating role of psychological distress on IPV perpetration. Practical implications for intervention policies in IPV perpetration will be discussed.